Micro Biostratigraphy and Lithostratigraphy of the Upper Permian Dalan Formation (Zagros Basin, Southwest Iran) - Rafiee, Pedram; Baghbani, Dariush; Aghanabati, Ali; Arian, Mehran (International Journal of Geography and Geology, 2014)
The objective of the present study is to perform Microbiostratigraphy and Lithostratigraphy of the Upper Permian Dalan Formation at a Well (Well 1) in the Zagros Basin. The Upper Permian Dalan Formation contains vast gas reservoirs in the southwest Iran and is composed of three Members: The Lower Dalan Member corresponds to Wordian to Capitanian; the Nar Member is latest Capitanian and the Upper Dalan Member corresponds to Wuchiapingian to Changhsingian. Lower and Upper Dalan Members include mainly limestone, dolomitic limestone and Nar member mostly consists of anhydrite and thin interlayer of dolomite. The biostratigraphic study allows individualizing Foraminifers from the Wordian to the Changhsingian (Middle to Late Permian). Based on the stratigraphic distributions of the Biostratigraphically significant fauna and flora the following 7 biozones and age determinations are proposed in the Upper Permian Dalan Formation: 7. Paraglobivalvulinoides septulifera zone (Changhsingian) 6. Paradagmarita zone (Changhsingian) 5. Rectostipulina zone (Wuchiapingian) 4. Shanita zone (Capitanian) 3. Paraglobivalvulina zone (Capitanian) 2. Globivalvulina zone (Wordian) 1. Eoverbeekina zone (Wordian)